A note on the impact of options on stock return volatility - Bollen, Nicolas P.B. (Journal of Banking & Finance, 1998)
This paper measures the impact of option introductions on the return variance of underlying stocks. Past research generally finds a significant reduction in stock return variance following the listing of options through 1986. Using a more extensive sample, I compare changes in the return variance of optioned stocks to changes in the return variance of a control group. Since the average change in the control group is statistically indistinguishable from the average change in the optioned stocks, I conclude that option introductions do not significantly affect stock return variance.